Roles of positive psychological capital resources dimensions on self-employment creation among youths - Yonla, Maklu Nanteer; Auta, Habila Dogo; Katunku, Fredrick Longwul; Dafeng, Tongshakap Gyang (Journal of Sustainable Tourism and Entrepreneurship, 2024)
Purpose: This research paper aims to explore how positive psychological resources influence youth participating in the Industrial Training Fund’s (ITF) National Industrial Skill Development Programme (NISDP), specifically examining the programs’ impact on self-employment creation in Plateau State, Nigeria. Method: The paper employs Confirmatory Factor Analysis (CFA) and a Structural Equation Model (SEM) to examine the relationship between positive psychological resources and self-employment creation in Plateau State. Results: The study concludes that dimensions of positive psychological resources serve as effective predictors of self-employment creation among youths. However, it notes that two dimensions; resilience and hope, did not exhibit a significant positive relationship. Nonetheless, the lack of significance does not negate the existence of a relationship explaining self-employment creation among youths in the context of this study. Limitations: Several factors constrained the study. It was conducted within a specific constituency in Plateau State, limiting its scope and generalizability. Therefore, the results may not be applicable to the entire state. Contributions: This study offers insights beneficial to both self-employed and unemployed youths, emphasizing the importance of a positive mindset in self-employment creation. The findings are particularly relevant to the Industrial Training Fund (ITF) and its National Industrial Skills Development Programme (NISDP), shedding light on the effectiveness of their training programs fostering self-employment. Moreover, this research contributes to the existing body of literature on self-employment creation among youths and extends understanding of positive psychological capital resources (PSYCAP) by examining various dimensions. Additionally, it provides guidance for future directions in research and practice in this field.